Upaya – Upaya Dalam Pencegahan Terjadinya Pelecehan Seksual Di Sekolah Dasar Negeri 070985 Onowaembo Kota Gunungsitoli - Hidayat Laoli; Sukaaro Waruwu; Syah Abadi Mendrofa; Yamolala Zega (Journal on Education, 2024)
In this study, researchers conducted environmental observations at SD Negeri 070985 Onowaembo school, Gunungsitoli District, to obtain information data on the extent of efforts to prevent sexual harassment carried out by teachers and school management. In this study, conducting qualitative methods by conducting interviews with informants. The purpose of this study was to determine the efforts made by the school management in preventing sexual harassment as well as the school's attitude and responsibility for harassment of students at SD Negeri 070985 Onowaembo Kota Gunungsitoli. The results of the study, researchers found that there are rules and regulations involving the prohibition of sexual harassment, security supervision, ensuring the safety and comfort of students, as well as cooperation between school committees and parents for child supervision and protection, increasing religious values through monthly worship activities, cooperation with the Child Protection Commission for education on children's rights, understanding child protection rights through learning curricula, implementation of extracurricular activities such as art and discussion, as well as facilitation of sanitation according to gender. Firm policies and rules, support for all parties and supervision for students as well as teacher involvement, supervision and security control during school activities.